2014
DOI: 10.1016/j.biomaterials.2014.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Thiol-ene hydrogels as desmoplasia-mimetic matrices for modeling pancreatic cancer cell growth, invasion, and drug resistance

Abstract: The development of pancreatic ductal adenocarcinoma (PDAC) is heavily influenced by local stromal tissues, or desmoplasia. Biomimetic hydrogels capable of mimicking tumor niches are particularly useful for discovering the role of independent matrix cues on cancer cell development. Here, we report a photo-curable and bio-orthogonal thiol-ene (i.e., cross-linked by mutually reactive norbornene and thiol groups via photoinitiation) hydrogel platform for studying the growth, morphogenesis, drug resistance, and can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
71
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(78 citation statements)
references
References 46 publications
(53 reference statements)
6
71
0
1
Order By: Relevance
“…Our study demonstrated the association between elevated YAP1 expression and poor clinicopathologic phenotype in bladder cancer specimens and suggested that this might be a useful marker for diagnosis. In addition, YAP1 has been shown to function in different ways [23][24][25], including abrogation of contact inhibition and promotion of the epithelial-mesenchymal transition [4,26]. Accordingly, our results showed that YAP1 dramatically increased bladder cancer cell proliferation and migration in vitro.…”
Section: Discussionsupporting
confidence: 48%
“…Our study demonstrated the association between elevated YAP1 expression and poor clinicopathologic phenotype in bladder cancer specimens and suggested that this might be a useful marker for diagnosis. In addition, YAP1 has been shown to function in different ways [23][24][25], including abrogation of contact inhibition and promotion of the epithelial-mesenchymal transition [4,26]. Accordingly, our results showed that YAP1 dramatically increased bladder cancer cell proliferation and migration in vitro.…”
Section: Discussionsupporting
confidence: 48%
“…19 For example, an enzymatically degradable polyethylene glycol hydrogels with orthogonally controlled biophysical and biochemical properties have been developed for the study of pancreatic ductal adenocarcinoma. 58 When collagen was added to the matrix (i.e. in the presence of cell attachment), there was a greater cell spreading and an up-regulation of membrane type 1-matrix metalloproteinase 1 (MT1-MMP; i.e.…”
Section: Biomaterials For Csc Growthmentioning
confidence: 99%
“…58 Interestingly, irrespective of collagen presence, cells cultured in 3D matrices developed chemo-resistance, likely as a consequence of the enrichment of pancreatic CSCs that expressed high levels of CD24, sonic hedgehog (a protein that controls cell division of adult stem cells and is implicated in the development of some cancers), and VEGF. 58 Lastly, fibrous electrospun polycaprolactone scaffolds have been tested for the expansion of breast cancer cells and showed an increased proportion of CSCs. 59 Moreover, an upregulation of EMT and increased invasive capability were observed in cells cultured on fibrous scaffolds.…”
Section: Biomaterials For Csc Growthmentioning
confidence: 99%
“…While tissue-engineered models of other cancers have been developed (e.g., non-small cell lung cancer, [32,33] PDAC (pancreatic ductal adenocarcinoma), [34] hepatocellular carcinoma, [35][36][37] oral squamous cell carcinoma, [38] prostate cancer, [39,40] ovarian cancer [41][42][43] ), these examples were selected to highlight the role of materials innovation in developing hydrogel-based 3D tissue-engineered models.…”
Section: Examples Of Tissue-engineered Cancer Modelsmentioning
confidence: 99%